Youth Tobacco Survey among the School Going Adolescents in a Block of Vadodara District, Gujarat. - Patel, Geetika M; Zalavadiya, Dhara L; Thomas, Ebbie; Jha, Ranjit K; Godara, Naresh R; Patel, Nikhil J (Indian Journal of Community Health, 2018)
Background: Tobacco use is the leading cause of Preventable death, Tobacco use during adolescence increases the risk of persistent addiction, leading to regular and sustained tobacco use in adulthood. Objective: To assess the prevalence and practice of tobacco use among the school going adolescents in a block of Vadodara district, Gujarat. Material & Methods: Multiphase sampling was done to select the sample students (13 to 17 years) from private and government schools in a selected block of Vadodara. A cross-sectional study including 1045 students was carried out using a pre-designed and pre-tested proforma. Results: Out of 1045 students, 3% (n=32) tried cigarette smoking ever, one or two puffs and 1.8% (19 students) of students were current cigarette or beedi smokers. Around 27.9% students and 23% students admitted that at least one of their parents and friends smoked cigarettes, respectively. About 24% and 44% of the students were exposed to passive smoking at home and outside home, respectively. Conclusions: Present study provides the baseline information of prevalence of smoking and attitude of school going adolescents towards smoking in Gujarat. The result gives an alarm to work upon tobacco control among adolescents and make them aware about the hazards.